Molecular Characterization and Meta-Analysis of Gut Microbial Communities Illustrate Enrichment of Prevotella and Megasphaera in Indian Subjects - Bhute, Shrikant; Pande, Pranav; Shetty, Sudarshan A.; Shelar, Rahul; Mane, Sachin; Kumbhare, Shreyas V.; Gawali, Ashwini; Makhani, Hemal; Navandar, Mohit; Dhotre, Dhiraj; Lubree, Himangi; Agarwal, Dhiraj; et al. (Frontiers in Microbiology, 2016)
The gut microbiome has varied impact on the wellbeing of humans. It is influenced by different factors such as age, dietary habits, socio-economic status, geographic location and genetic makeup of individuals. For devising microbiome-based therapies, it is crucial to identify population specific features of the gut microbiome. Indian population is one of the most ethnically, culturally and geographically diverse, but the gut microbiome features remain largely unknown. The present study describe gut microbial communities of healthy Indian subjects and compares it with the microbiota from other populations. Based on large differences in alpha diversity indices, abundance of 11 bacterial phyla and individual specific OTUs, we report inter-individual variations in gut microbial communities of these subjects. While the gut microbiome of Indians is different from that of Americans, it shared high similarity to individuals from the Indian subcontinent i.e. Bangladeshi. Distinctive feature of Indian gut microbiota is the predominance of genus Prevotella and Megasphaera. Further, when compared with other non-human primates, it appears that Indians share more OTUs with omnivorous mammals. Our metagenomic imputation indicates higher potential for glycan biosynthesis and xenobiotic metabolism in these subjects. Our study indicates urgent need of identification of population specific microbiome biomarkers of Indian subpopulations to have more holistic view of the Indian gut microbiome and its health implications.